Gel Ekstrak Daun Sirsak (Annona muricata L.): Formulasi dan Efektivitas terhadap Microsporum canis - Rahmawati, Juwita; Nastiti, Amaranggana Lalita; Setiyadi , Gunawan; Maulana , Farrel (Journal of Pharmaceutical and Sciences, 2025)
Soursop (Annona muricata  L.) leaves contain genistein, steroids, and coumarins, which exhibit potential as natural antifungal agents against Microsporum canis, the causative agent of ringworm. This study aimed to formulate a soursop leaf extract gel using Na-CMC and carbopol 940 as gelling agents, optimized through the Simplex Lattice Design (SLD) with DE version 13, and to evaluate its physical characteristics and antifungal activity. Extraction was carried out by maceration with 96% ethanol. The optimum formula was obtained with 4.3% Na-CMC and 1.7% carbopol 940. The optimized gel exhibited homogeneous texture, characteristic soursop odor, greenish-brown semi-solid appearance, pH of 6.56 ± 0.17, viscosity of 326 ± 16.73 dPas, spreadability of 3.96 ± 0.43 cm², and adhesiveness of 1.58 ± 0.71 seconds. Antifungal testing using the well diffusion method showed an inhibition zone of 15.33 mm, classified as strong activity. ANOVA analysis revealed a significance value of 0.000 (< 0.05), indicating significant differences among the positive control, negative control, optimized gel, and soursop leaf extract. The antifungal activity of the optimum formula was not significantly different from that of the soursop leaf extract (p = 0.795). These results indicate the potential of soursop leaf extract gel as an effective antifungal alternative.